A randomized controlled trial of simulation‐based mastery learning to teach the extended focused assessment with sonography in trauma. Issue 3 (18th May 2021) - Smith, Siobhan; Lobo, Viveta; Anderson, Kenton L.; Gisondi, Michael A.; Sebok‐Syer, Stefanie S.; Duanmu, Youyou
Abstract: Background: Mastery learning has gained popularity for training residents in procedural skills due to its demonstrated superiority over traditional methods. However, no studies have compared the efficacy of traditional versus mastery learning methods in residency point‐of‐care ultrasound education. We hypothesized that mastery learning would improve residents' skills in performing the extended focused assessment with sonography in trauma (eFAST). Methods: All first‐year emergency medicine (EM) resident physicians at a single university hospital underwent a crossover randomized controlled trial to receive mastery‐learning eFAST training either at the beginning of the academic year or 6 months into intern year. Participants were taught using a checklist validated by a panel of experts using Mastery Angoff methods and were given feedback on missed tasks until each trainee completed the eFAST with a minimum passing standard (MPS). Our primary outcome was technical proficiency between the two groups for eFAST examinations performed in the emergency department during the academic year. Results: Sixteen interns were enrolled; eight were randomized to each group. The group that received mastery training at the beginning of the year had mean clinical eFAST proficiency scores above the MPS in the first two quarters of the academic year, while the control group did not. Once the control group underwent eFAST mastery training at the midpoint of the year, both groups had mean proficiency scores above the MPS for the remainder of the year. Conclusion: Simulation‐based mastery learning is an effective method of teaching the eFAST examination. This training during intern orientation conferred early proficiency in clinical performance of eFAST among EM residents. This difference in proficiency was no longer present after the control group received mastery learning education halfway through the academic year.